‘Matrix’ images. Tapestries as precursors of digital images (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2020)
The reproduction of images can involve processes of translation into codes that, through particular technological devices, can then allow to replicate it. Among the possible codes that can have this function, one in particular seems to be particularly adequate for the transmission of information and therefore also of images: the matrix, certainly understood in its most classical sense as an ordered table of elements, but whose etymology suggests other meanings besides the purely mathematical one. The word ‘matrix’ not only identifies a rectangular table of symbols arranged in rows and columns, but also distinguishes that which gives origin, which can allow the production of several copies from an original. Therefore, ‘matrix images’ can be defined as the ones that are conceived and reproduced with the help of matrices, understood as ordered systems of elements organized according to a table of rows and columns, in which symbols belonging to that code that allows the conversion of the matrix back into an image. Although this kind of images has a millennial history, characterized by the succession of experiments on different materials and technological solutions, it can be highlighted invariants. Starting from the analysis of some significant relationships between products, methods and production strategies that are distant in time and space, such as those that can be hypothesized between textile and digital visual artifacts, this article analyzes the drawings made by means of knots, weaves, pixels, dots and all those minimal elements capable of reproducing images designed through matrices and visualized through the intermediation of technological tools such as looms, printers and screens, which outline the genealogy of a technique of production and reproduction of images that is always current.
Keywords: digital images; matrices; textiles